Diagnóstico de los niveles de emisión de amoníaco en granjas de pollos broiler del cantón Bolívar, Manabí – 2021 - Nevárez Loor, Alex Jamil (2022)
The objective of this research was to diagnose ammonia emission levels in Boiler chicken farms registered both in AGROCALIDAD and the Decentralized Autonomous Government of the Bolívar canton located in the province of Manabí. The factor under study was the valuation of ammonia in each one of the farms. As part of the diagnosis, a survey and interview were carried out. The experimental units were six poultry farms located within the area of Cantón Bolívar. The variables evaluated by non-parametric analysis were the characteristics of farm management and chicken rearing, ammonia levels and the percentage of morbidity due to respiratory diseases. As a main result and in relation to the characterization, it was obtained that almost all farms use the same management and raising of chickens. On the other hand, the ammonia emission levels in all the farms did not exceed 13 ppm, so they were low and comply with the established limit (<20 ppm). Finally, farms five and three presented the highest percentages of morbidity within the present study, however, this morbidity is within low standards.